Peran Sistem Pengendalian Manajemen dalam Meningkatkan Kinerja Organisasi: Studi Empiris pada Organisasi Sektor Jasa di Indonesia - Tour Hidayah Harahap (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to examine the role of Management Control Systems (MCS) in improving organizational performance within service sector organizations in Medan City, Indonesia. A quantitative approach with an explanatory research design was employed. Data were collected through questionnaires distributed to 150 respondents selected using a purposive sampling technique. The independent variable was the Management Control System, measured through five dimensions: strategic planning, budgeting, operational control, management information systems, and performance evaluation. Organizational Performance served as the dependent variable. Data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis with IBM SPSS Statistics version 27. The findings reveal that Management Control Systems have a positive and significant effect on Organizational Performance, both partially and simultaneously. Among the dimensions examined, operational control contributed the most to improving organizational performance. The coefficient of determination indicates that Management Control Systems explain 61.3% of the variance in Organizational Performance. These findings demonstrate that an integrated Management Control System, supported by effective management information systems and continuous performance evaluation, plays a crucial role in enhancing organizational effectiveness, operational efficiency, productivity, and service quality. This study contributes to the development of management accounting literature and provides practical recommendations for organizations to strengthen management control systems in achieving sustainable strategic objectives.